Hubungan Antara Hasil Belajar Dengan Perilaku Etika Sopan Santun di Rumah Siswa Kelas VI SD Muhammadiyah Gamping Sleman - luluk tariyanti; Muhamad Sofian Hadi (CENDEKIAWAN, 2025)
This study was prompted by the low level of students' etiquette and politeness. Students were observed speaking impolitely to their peers, teachers, and elders. The education of moral etiquette should not only be implemented and practiced in schools but also within the students' family environment. The purpose of this study was to determine the relationship between the learning outcomes of moral etiquette education at school and the polite behavior of sixth-grade students towards their families at SD Muhammadiyah Gamping, Sleman, during the 2017/2018 academic year. This study employed a descriptive quantitative research design. The approach used for data analysis was quantitative, utilizing the product-moment correlation technique. The results of the correlation analysis and hypothesis testing indicated a relationship between the learning outcomes of moral etiquette education at school and students' polite behavior towards their families. The correlation analysis showed that the calculated r-value (0.448) was greater than the table r-value (0.344), leading to the acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (Ho). These findings demonstrate a positive and significant relationship between the learning outcomes of moral etiquette education at school and the polite behavior of sixth-grade students towards their families at SD Muhammadiyah Gamping, Sleman.